An Analysis on Gender-Based Task in the Textbook Literature of Senior High School in Curriculum 2013 - Rusdin Rusdin (AL-FURQAN, 2016)
The aim of this paper is to investigate the gender-based task in the textbook literature of senior high school curriculum 2013 grade 10. This study used qualitative method in conducting the data from the textbook literature and this study analysis focus on the textbook of the 10 grade student only and the textbook consist of nine chapter. Based on the dialogue in the chapter I shows that there are two dialogues with no mixed of male and female, both of the dialogues are different in turns and amount of words many of turns and words are used by female then male. For chapter 4and 5, and 9 are balance meanwhile, in chapter 3, 6, and 7 are imbalance position of gender appearance in gender based-task. Meanwhile, on chapter 8 did not found any kinds of task that related to gender. Despite of that, gender based-task is appear with varieties activity such as gender position in doing dialogues, as personal pronoun he/she, firstness, pictures giving which include of gender occupation and family.